Pembulian dan Hukuman Dalam 2Raja-Raja 2:23-24: Analisis Teologis dan Etika Kristen di Era Kontemporer - Korwa, Frangky (MEFORAS: Jurnal Teologi dan Pendidikan Agama Kristen, 2025)
This research analyzes bullying and punishment in 2 Kings 2:23-24 with a Christian theological and ethical approach in a contemporary context. The main aim of the research is to understand the theological meaning behind the prophet Elisha's response to the offense he received and how Christian principles can be applied in dealing with bullying in the modern era. The main issue discussed is the relevance of this story to the phenomenon of social violence, especially in the form of bullying. The research method used is qualitative based on literature study with an exposition approach to interpret texts historically, linguistically and theologically. The novelty of this research lies in the integration of biblical studies with contemporary social issues, providing a new perspective on justice and love in dealing with bullying. The research results show that insulting Elisha was not just an individual act, but rather a collective collective reflection on divine authority. In the modern context, Christian teachings about love, forgiveness and respect for others are important guidelines in overcoming the phenomenon of bullying, both in direct interactions and in the digital world.